Intelektualiści w Europie Zachodniej: od sprawy Dreyfusa do wybuchu II wojny światowej - Tomczak, Maria (Studia Europaea Gnesnensia, 2011)
This article concerns the question of political engagement of the West-European intellectuals from the Dreyfus Affair (1898) to the Second World War. After the Second World War, the European intellectuals attempted to resort to the mode of action elaborated by Dreyfus’ advocates and defenders outside the courtroom. Nevertheless, the success had not been achieved again. The European intellectuals failed to repeat the accomplishment through the lack of political experience, submission and dependence. Their intellectual efforts for Europe cannot be positively evaluated and did more harm than good.